Efficacy of Qigong Exercise for Treatment of Fatigue: A Systematic Review and Meta-Analysis - Wang, Rui; Huang, Xueyan; Wu, Yeqi; Sun, Dai (Frontiers in Medicine, 2021)
Objective: Several studies suggested that Qigong exercise (QE) can relieve fatigue in patients diagnosed with various diseases. Our review aimed to evaluate the efficacy of QE for alleviating fatigue. Methods: A related literature search was performed in the PubMed, Web of Science, Embase, Cochrane Library, China Biology Medicine disc (CBM), China National Knowledge Infrastructure (CNKI), Wanfang, and VIP data bases from inception to November 2020. Information on fatigue, malaise, tiredness, and Qigong research data was collected. Results: Sixteen randomized controlled trials (RCTs) were reported in patients with cancer (n = 4), chronic fatigue syndrome (n = 2), and other diseases (n = 10). The QE groups showed significant improvements in total fatigue intensity (15 RCTs, p < 0.00001; standard mean difference (SMD) -0.69 [-0.95 to -0.44]). The QE groups did not show significant improvement in quality of life (4 RCTs, p = 0.08; SMD 0.53 [-0.07 to 1.14]). The statistically significant difference of the subgroup analyses (different primary diseases, QE types, and study quality) also remained unchanged. Conclusion: The findings of this meta-analysis indicate that QE may be beneficial for improving fatigue in patients diagnosed with various diseases. Considering the limitations of the study, we draw a very cautious conclusion regarding the resulting estimate of the effect. Further studies are warranted to better understand the benefits of QE in primary medical care.